A Simplified Proof of Uncertainty Principle for Quaternion Linear Canonical Transform - Mawardi Bahri; Ryuichi Ashino (Abstract and Applied Analysis)
We provide a short and simple proof of an uncertainty principle associated with the quaternion linear canonical transform (QLCT) by considering the fundamental relationship between the QLCT and the quaternion Fourier transform (QFT). We show how this relation allows us to derive the inverse transform and Parseval and Plancherel formulas associated with the QLCT. Some other properties of the QLCT are also studied.